Analisis Perbandingan dan Faktor-Faktor Yang Mempengaruhi Kinerja Akademik Mahasiswa UPBJJ-UT Bengkulu - Mikaresti, Pamela; Yusrizal, Yusrizal; Nurmalia, Ana (Universitas Pendidikan Mandalika, 2023)
This research aims to compare the factors that influence students' academic achievement in learning assistance services (TUWEB, TUTON, TMK) at UPBJJ-UT Bengkulu. This research used a descriptive method with a quantitative approach. The total population in this study was 11,854 people, with a sample of 1185 respondents. The research instrument used was a questionnaire with the data analysis technique for this research using multiple linear regression analysis. The results of this research showed that the overall cumulative achievement index of respondents had the highest average GPA obtained by TUWEB service users, namely 3.56, and the lowest was the average GPA of TMK service users was 3.21, while the average GPA of TUTON learning assistance service users was 3.40. The variables of learning motivation, learning assistance, and learning media influence the Grade Point Average (GPA). Meanwhile, the independent variables that do not partially affect the Grade Point Average (GPA) were age, marital status, employment status, participation in academic service assistance, level of perception towards UT, and the independent learning system and network quality.